Melatonin Alleviates the Suppressive Effect of Hypoxanthine on Oocyte Nuclear Maturation and Restores Meiosis via the Melatonin Receptor 1 (MT1)-Mediated Pathway - Wang, Jing; Zhuo, Zhiyong; Ma, Xiao; Liu, Yunjie; Xu, Jing; He, Changjiu; Fu, Yao; Wang, Feng; Ji, Pengyun; Zhang, Lu; Liu, Guoshi (Frontiers in Cell and Developmental Biology, 2021)
It is well known that hypoxanthine (HX) inhibits nuclear maturation of oocytes by elevating the intracellular cAMP level, while melatonin (MT) is a molecule that reduces cAMP production, which may physiologically antagonize this inhibition and restore the meiosis process. We conducted in vitro and in vivo studies to examine this hypothesis. The results showed that 10-3 M MT potentiated the inhibitory effect of HX on mouse oocyte meiosis by lowering the rate of germinal vesicle breakdown (GVBD) and the first polar body (PB1). However, 10-5 M and 10-7 M MT significantly alleviated the nuclear suppression induced by HX and restored meiosis in 3- and 6-week-old mouse oocytes, respectively. We identified that the rate-limiting melatonin synthetic enzyme AANAT and melatonin membrane receptor MT1 were both expressed in oocytes and cumulus cells at the GV and MⅡ stages. Luzindole, a nonselective melatonin membrane receptor antagonist, blocked the activity of MT on oocyte meiotic recovery (P<0.05). This observation indicated that the activity of melatonin was mediated by the MT1 receptor. To understand the molecular mechanism further, MT1 knockout (KO) mice were constructed. In this MT1 KO animal model, the PB1 rate was significantly reduced with the excessive expression of cAPM synthases (Adcy2, Adcy6, Adcy7 and Adcy9) in the ovaries of these animals. The mRNA levels of Nppc and Npr2 were upregulated while the genes related to progesterone synthesis (Cyp11a11), cholesterol biosynthesis (Insig1) and feedback (Lhcgr, Prlr, Atg7) were downregulated in the granulosa cells of MT1 KO mice (P<0.05). The altered gene expression may be attributed to the suppression of oocyte maturation. In summary, melatonin protects against nuclear inhibition caused by HX and restores oocyte meiosis via MT1 by reducing the intracellular concentration of cAMP.